EFEKTIVITAS PENGGUNAAN STRATEGI PEMBELAJARAN POINT COUNTER POINT DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS VIII DI MADRASAH TSANAWIYAH AR RAHMAN LARANGAN SLAMPAR TLANAKAN PAMEKASAN - Siti Horrifah; Moh Subhan (Journal of Education Partner, 2023)
Two problems are the main study of this research, the first is due to the low learning achievement of students, and the second is due to the lack of interest in learning and understanding of students, class VIII at the Ar-Rahman Larangan Slampar Tlanakan Pamekasan tsanawiyah madrasah. The problem formulation in this research is: 1). What is the effectiveness of using the Point Counter Point learning strategy in improving student learning achievement in class VIII fiqh subjects at the Ar Rahman Tsanawiyah Madrasah Larangan Slampar Tlanakan Pamekasan?, 2). What are the supporting and inhibiting factors for using the point counter point learning strategy in improving student learning achievement in class VIII fiqh subjects at the Ar Rahman Prohibition of Slampar Tsanawiyah Madrasah? This research uses a qualitative descriptive approach where the research results obtained are in the form of descriptive data, the data sources for this research are the school principal, Fiqh subject teachers, and also students. Meanwhile, data analysis was carried out in a qualitative descriptive manner by reducing data, presenting data, and verifying the data obtained. The research results obtained show that the Point Counter Point learning strategy is quite effective in improving student learning achievement in class VIII Madrasah Tsanawiyah Ar Rahman. This is proven by the supporting factors, namely students feel enthusiastic, feel comfortable, feel happy, feel not bored, increasing student learning achievement is also supported by the existence of adequate learning media facilities at the Madrasah Tsanawiyah Ar Rahman institution. while the inhibiting factors are students' lack of awareness of the importance of formal education and the fatigue factor.